PERTANIAN ORGANIK; MENUJU PENINGKATAN KEAMANAN DAN KETAHANAN PANGAN MASYARAKAT - Shofia Nur Awami (MEDIAGRO, 2008)
Food materials as elementary requirement, these are the source of human being body nutrient. But in food materials, this way natur and alsomicrobe contaminate, many there are poisonous compound. Go together foodand availability, many case which have emerged concern poisoning of food andugly nutrient case. Lower of society attention to food security result casepoisoning of food in Indonesia often happen. The return applying of expectedorganic agriculture system can depress case number poisoning of food, besidethere are other advantage which can be obtained by like; decreasing of itenvironmental contamination, the return of ground fertility cycle, etc. Besidescentral government, relevant institutes like Department Agriculture,Departmental of Oceaninc And Fishery, of Industry and Commerce, Localgovernment, Body POM; they have claimed to always to share and also ingiving construction, counselling, monitoring and inspection circulation of foodmaterials. So that, the food materials which were accepted by society /consumer, peaceful and its quality was lawful well guaranted and also wasconsumed. Keyword : Organic agriculture, Food security, Poisoning of food